Genetic counseling in veterinary medicine: towards an evidence-based definition for the small animal practice - Laura Adant; Virginie Szymczak; Sofie F. M. Bhatti; Pascale Smets; Jimmy Saunders; Luc Peelman; Bart J. G. Broeckx (BMC Veterinary Research, 2025)
Abstract Background In human medicine, questions regarding heritable disorders are dealt with by clinical geneticists and genetic counselors and both the field, their roles and the tools they use are well-defined. Even though the prevalence of diseases is far higher and scientific literature agrees on expectations towards an increased importance, this does not seem to be the case in veterinary medicine. While we hypothesize that there will be an overlap, some characteristics uniquely linked to veterinary medicine might not be covered. Methods To investigate this in-depth and in an attempt to define the field, we compared the internationally accepted definitions and its subparts on genetic counseling in human medicine with what is found in veterinary literature and what was seen in cats and dogs presented at our dedicated small animals clinical genetics/genetic counseling clinic. The results were used in a stepwise analysis that lead to a set of three potential definitions (i.e. on what genetic counseling is, who provides it and which tools are used) that fullfill four criteria (i.e. definitions have to be clear/self-explanatory, minimally sufficient, complete and valid). Results The short version of the definition of genetic counseling in veterinary medicine is: "Genetic counseling is the process of helping animal owners and breeders understand – and adapt to – the medical, psychological, familial implications of genetic contributions to disease.” Genetic counseling in small animal practice is currently provided by veterinarians and the tools that are used, can be divided in five categories. The signalment of the patients revealed that both cats (30%) and dogs (70%) and various breeds, the two sexes (37% males, 63% females) and all age categories (puppy/kitten—senior) were represented. Furthermore, 73% of the patients were referred by or needed to be referred to other disciplines. Conclusion These definitions are derived from human and veterinary literature, and an evaluation based on patient data has demonstrated that these definitions meet all the criteria of a correct definition (i.e. clear, minimally sufficient, complete and valid). With these definitions and case descriptions, our aim is to contribute to the formal foundation of genetic counseling in veterinary medicine.